Bifunctional atomically dispersed ruthenium electrocatalysts for efficient bipolar membrane water electrolysis. Issue 16 (1st July 2022) - Yu, Zhipeng; Si, Chaowei; Escobar-Bedia, Francisco Javier; LaGrow, Alec P.; Xu, Junyuan; Sabater, Maria J.; Amorim, Isilda; Araujo, Ana; Sousa, Juliana P. S.; Meng, Lijian; Faria, Joaquim Luis; Concepcion, Patricia; et al.
Abstract : Bifunctional atomically dispersed ruthenium electrocatalysts with a low metal loading (0.2 wt%) exhibit outstanding performance for bipolar membrane water electrolysis. Abstract : Atomically dispersed catalysts (ADCs) have recently drawn considerable interest for use in water electrolysis to produce hydrogen, because they allow for maximal utilization of metal species, particularly the expensive and scarce platinum group metals. Herein, we report the electrocatalytic performance of atomically dispersed ruthenium catalysts (Ru ADCs) with ultralow Ru loading (0.2 wt%). The as-obtained Ru ADCs (Ru (0.2)-NC) are active for both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), which only require a low overpotential ( η ) of 47.1 and 72.8 mV to deliver 10 mA cm −2 for HER in 0.5 M H2 SO4 and 1.0 M KOH, respectively, and of 300 mV for OER in 1.0 M KOH, showing favorable bifunctionality. Density functional theory (DFT) calculations reveal that the Ru–N bonding plays an important role in lowering the energy barrier of the reactions, boosting the HER and OER activities. Furthermore, the bipolar membrane (BPM) water electrolysis using the bifunctional Ru (0.2)-NC as both HER and OER catalysts can afford 10 mA cm −2 under a low cell voltage of only 0.89 V, and does not show any performance decay upon 100 h continuous operation, showing great potential for energy-saving hydrogen production.